The Visuality of the Holocaust Today - Mayer, Gabriel (Advances in Social Sciences Research Journal, 2019)
The Visuality of the Holocaust Today By invoking the term Visuality, I am quite intentionally referring to the optical encounter with Holocaust representation in today’s world.This notion is a reaction to the common adage that states, people don’t want to read the book, they want to see the movie. Holocaust representation in this visual sense is primarily encountered in museums, the cinema, and the fine arts such as painting and sculpture. This latter category, by its virtuality as a highly subjective presentation, is better left for another discussion. On the other hand, and while acknowledging the primary significance of Holocaust historical literature, there is little argument that in the present times the most frequent encounter by the public in regards to this subject matter occurs most often in a museum or at the cinema. Therefore it behooves us to examine the public’s experience and compare it to the historical realities. The purpose of this work is to examine the historical evolution of the current state of affairs, and it is a challenging task. The final goal is to contribute to the preservation of honesty, historical accuracy, and, most of all the integrity of the memory of the Holocaust.